The perceptions of KUIM’s (Kolej Universiti Islam Malaysia) first year undergraduates in learning English using ‘tell me more’ software - Zakaria, Zarina Ashikin (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
The use of technology in language learning has expanded rapidly worldwide during the last few decades. Studies on the effects of technology enhanced instruction on achievement and studies on students’ attitudes regarding learning with technology have also increasingly been reported (Salaberry, 2001). Technology includes computermediated communication via email, incorporated task-based Internet activities,interactive publisher-produced CD-ROM, interactive software, threaded discussions and many others. This paper focuses on the perceptions of students at Kolej Universiti Islam Malaysia (KUIM) towards learning English as a second language using ‘Tell Me More’ software. This software has been used in KUIM for many years and for the past few semesters, it has been made compulsory for all first year undergraduates to self-access the software for at least an hour per week. Various feedbacks were received but most of the responses were positive. Most of the respondents favoured learning English using the software, but they still preferred conventional classroom English lessons.